The Relationship of Plasmodium sp Density to Platelet Count and Hemoglobin Levels in Malaria Patients at Bhayangkara Hospital TK I Pusdokkes Police Kramat Jati, Indonesia - Inderiati, Dewi; Oktapıa, Nısa; Nida, Wadhatun; Zuraida, Zuraida; Hariutami, Desi (Medical Laboratory Technology Journal, 2024)
Malaria is an acute and chronic disease. Globally, as many as 247 million positive cases of malaria were reported in 84 malaria-endemic countries. Indonesia is a malaria-endemic country with a total of 443,530 cases with a malaria prevalence of 89% reported from Papua province. This study examined the correlation between Plasmodium sp density platelet count and hemoglobin levels. The type of research used in this study was observational analytics with a cross-sectional study approach design. The sample and population in this study were malaria-positive patients who had their platelet count and hemoglobin levels checked as recorded in the report from Bhayangkara Hospital Tk I Pusdokkes Polri Kramat Jati, Indonesia, namely using medical record data from months January to December a total of 54 samples with data analysis in this study using descriptive univariate analysis and bivariate analysis using the Fisher Exact test. This study showed that the density of Plasmodium sp with the number of platelets had a significant result, namely 0.088, which indicates that the density of Plasmodium sp does not affect the platelet count. In contrast, the density of Plasmodium sp with hemoglobin levels had a significant result, namely 0.023, which indicated a lower Hb level of malaria sufferers. The higher the level of Plasmodium density.